Assisting with urinary elimination - Johnson, Joyce Young; J. B. Lippincott Company (Philadelphia, Pa. : Lippincott-Raven Publishers, 1997)
(Producer) Skills focus on assisting with toileting, inserting a straight and indwelling urinary catheter, administering catheter care, and removing an indwelling catheter. Also include are important tips for the nurse who is caring for the client with an indwelling catheter, whether in a hospital, long-term care setting or home setting.
Videocassette is available at Koleksi Media, PHUKM
Keywords: Urinary Catheterization -- nursing; Urinary Catheterization -- methods; Urination